Single-port video-assisted thoracoscopic surgery (VATS) excision of paravertebral ganglioneuroma: a case report - Domjan, Matic; Štupnik, Tomaž (Video-Assisted Thoracic Surgery; Vol 1 (November 2016): Video-Assisted Thoracic Surgery, 2016)
Video-assisted thoracoscopic surgery (VATS) resection is the procedure of choice, when it comes to resection of benign neurogenic tumours in the paravertebral space, however there are only few reports of single-port VATS resection of paravertebral masses. We present a case of a 32-year-old female with Ganglioneuroma in the right paravertebral space. A single-port VATS resection of the tumour was performed and no chest tube was left in the pleural cavity, which made it possible for the patient to be discharged on postoperative day 1 after an uneventful postoperative recovery.